A Study on Growth and development of Pre-primary Education in Assam A Status Report - Roy, Sumona; Saikia, Rasmi Rekha (JOURNAL OF INDIAN EDUCATION, 2014)
Pre- primary education is the basic foundation upon which a child’s educational and social, personal habits and values stand. Therefore, the stronger this foundation, the stronger the child will emerge in education and personality development. The national policy makers’ awareness to this fact is reflected in formulation of various policies and directives in post colonial era. The state of Assam also witnessed a drastic change in early childhood education. Although the concept of Pre-primary education was evident in this state in few institutions since pre-independence era but the education system is devoid of a proper pre-school education system for children. It lacks not only the structural requirements of a minimum Pre-primary infrastructure but also the functional requirement of a formal Pre-primary teacher’s education. However, remarkable efforts are being made at the government level through the SCERT, Assam and Sarva Siksha Abhijan (SSA), Assam for proper functioning and proper implementation of Pre-primary education in respect to teacher training, material development for classroom transaction, monitoring and evaluation system, etc. Various policies and programmes formulated by the Government of India as well as Government of Assam which were implemented in the state have been critically reviewed.